Cover Feature: Tracking Subtle Membrane Disruptions with a Tethered Photoacid (ChemPhotoChem 8/2020). Issue 8 (14th August 2020) - Amdursky, Nadav; Lin, Yiyang
Abstract : The Cover Feature illustrates the working principle of a novel fluorescent dye for biological membranes. This probe lights up within membranes, and its unique feature is its ability to sense events taking place on the membrane far away from the probe location. This is due to the photoacidity of the probe, which initiates a proton diffusion process on the membrane surface upon light‐induced proton dissociation from the probe. Subtle disruptions in the membrane integrity influence the proton diffusion process, and consequently change the fluorescent properties of the probe. More information can be found in the Article by Nadav Amdursky and Yiyang Lin .